Prevalent hepatitis B surface antigen among first-time blood donors in Gabon - Eko Mba, Jean Marie (PLoS One, 2018)
Despite chronic Hepatitis B virus (HBV) infection being the main cause of younger-onset complex liver disease including cirrhosis and hepatocellular carcinoma (HCC) in Africa, very little is known regarding the seroprevalence of HBV in the Gabonese general population. This investigation aimed to provide strong epidemiological data and risk factors associated with HBV infection in first-time blood donors representative of the urban adult population. The screening of HBsAg was carried out using 4th generation ELISA kits. The overall seroprevalence of HBsAg was 7.28%. The frequency of HBsAg was differential and marked by annual variations in blood donors from 2009 to 2016. Seroprevalence was 2-fold higher among males versus females (OR = 1.90 (95% CI: 1.75–2.06), P<0.001). HBsAg seroprevalence was significantly higher in donors of the age group 25–35 years old compared to donors of the age group <18 years (OR = 1.64 (95% CI: 1.03–2.60), P = 0.04). The seroprevalence of HBsAg in family/replacement donors (FRD) was significantly higher than that of voluntary non-remunerated donors (VNRD) (OR = 0.88 (95% CI: 0.83–0.94), P <0.001). The simultaneous comparison of HBsAg seroprevalence with blood donation type, gender and age showed that the higher prevalence in FRD was significant only in males between 18 and 45 years and in females between 25 and 34 years of age. This study confirms the high endemicity of HBV in Gabon while identifying the most infected age groups for both men and women.